Secretory carcinoma of the salivary gland, a rare entity: An international multi‐institutional study. Issue 9 (6th April 2022) - Wiles, Austin B.; Gabrielson, Matthew; Baloch, Zubair W.; Faquin, William C.; Jo, Vickie Y.; Callegari, Fabiano; Kholova, Ivana; Song, Sharon; Centeno, Barbara A.; Ali, Syed Z.; Tommola, Satu; Fadda, Guido; et al.
Abstract : BACKGROUND: Secretory carcinoma (SC) of the salivary gland is a rare entity with limited published literature on cytomorphology. The authors present the largest cohort to date of SC fine‐needle aspiration (FNA) cases. METHODS: FNA cases of histologically confirmed SC were retrospectively retrieved from 12 academic institutions in the United States, Italy, Finland, and Brazil. The collated data included patient demographics, imaging findings, cytopathologic diagnoses according to the Milan System for Reporting Salivary Gland Cytopathology, cytomorphologic characteristics, and immunohistochemical/molecular profiles. RESULTS: In total, 40 SCs were identified (male‐to‐female ratio, 14:26) in patients with a mean age of 52 years (age range, 13‐80 years). Ultrasound imagining revealed a hypoechoic, ovoid, poorly defined, or lobulated mass. The most common primary site was the parotid gland (30 of 40 tumors). Regional lymph node metastasis (9 patients) and distant metastasis (4 patients; brain, liver, lungs, and mediastinum) were noted. Two patients died of disease. FNA smears were cellular and demonstrated mainly large, round cells with intracytoplasmic vacuoles or granules and round‐to‐oval nuclei with smooth nuclear contour, minimal irregularities, and prominent nucleoli arranged predominantly in clusters, papillary formations, and single cells. The background was variable and contained inflammatory cells, mucin, or proteinaceous material. The diagnoses were malignant (19 of 38 tumors; 50%), suspicious for malignancy (10 of 38 tumors; 26%), salivary gland neoplasm of uncertain malignant potential (7 of 38 tumors; 18%), and atypia of undetermined significance (2 of 38 tumors; 6%) according to the Milan System for Reporting Salivary Gland Cytopathology. Two malignant cases (2 of 40 tumors; 5%) were metastases. The neoplastic cells were immunoreactive for S100 (23 of 24 tumors), mammaglobin (18 of 18 tumors), GATA‐3 (13 of 13 tumors), AE1/AE3 (7 of 7 tumors), and vimentin (6 of 6 tumors). ETV6‐NTRK3 fusion was detected in 32 of 33 tumors by fluorescence in situ hybridization (n = 32) and next‐generation sequencing (n = 1). CONCLUSIONS: Familiarity with cytomorphologic features and the immunohistochemical/molecular profile of SC can enhance diagnostic accuracy.; Abstract : Secretory carcinoma of the salivary gland, which may manifest with diverse cytomorphology, mammaglobin expression, and ETV6 rearrangement or ETV6‐NTRK3 fusion, was investigated along with cytomorphologic features to facilitate an accurate diagnosis. The results indicated that familiarity with these features and with the immunohistochemical/molecular profile of secretory carcinoma of the salivary gland enhanced diagnostic accuracy.